Effects of palm oil tocotrienol-rich fraction (TRF) and carotenes in ovalbumin (OVA)-challenged asthmatic Brown Norway rats - Zainal, Zaida; Abdul Rahim, Afiqah; Khaza'ai, Huzwah; Chang, Sui Kiat (MDPI, 2019)
Synthetic therapeutic drugs for asthma, a chronic airway inflammation characterised by strong eosinophil, mast cell, and lymphocyte infiltration, mucus hyper-production, and airway hyper-responsiveness, exhibit numerous side effects. Alternatively, the high antioxidant potential of palm oil phytonutrients, including vitamin E (tocotrienol-rich fractions; TRF) and carotene, may be beneficial for alleviating asthma. Here, we determined the therapeutic efficacy of TRF, carotene, and dexamethasone in ovalbumin-challenged allergic asthma in Brown Norway rats. Asthmatic symptoms fully developed within 8 days after the second sensitization, and were preserved throughout the time course via intranasal ovalbumin re-challenge. Asthmatic rats were then orally administered 30 mg/kg body weight TRF or carotene. TRF-treated animals exhibited reduced inflammatory cells in bronchial alveolar lavage fluid. TRF- and carotene-treated rats exhibited notable white blood cell reduction comparable to that from dexamethasone. TRF- and carotene-treatment also downregulated pro-inflammatory markers (IL-β, IL-6, TNF-α), coincident with anti-inflammatory marker IL-4 and IL-13 upregulation. Treatment significantly reduced asthmatic rat plasma CRP and IgE, signifying improved systemic inflammation. Asthmatic lung histology displayed severe edema and inflammatory cell infiltration in the bronchial wall, whereas treated animals retained healthy, normal-appearing lungs. The phytonutrients tocotrienol and carotene thus exhibit potential benefits for consumption as nutritional adjuncts in asthmatic disease.